Spruce Bark-Extracted Lignin and Tannin-Based Bioresin-Adhesives: Effect of Curing Temperatures on the Thermal Properties of the Resins - Sunanda Sain; Leonidas Matsakas; Ulrika Rova; Paul Christakopoulos; Tommy Öman; Mikael Skrifvars (Molecules, 2021)
In this study, formaldehyde-free bioresin adhesives were synthesised from lignin and tannin, which were obtained from softwood bark. The extraction was done via organosolv treatment and hot water extraction, respectively. A non-volatile, non-toxic aldehyde, glyoxal, was used as a substitute for formaldehyde in order to modify the chemical structure of both the lignin and tannin. The glyoxal modification reaction was confirmed by ATR–FTIR spectroscopy. Three different resin formulations were prepared using modified lignin along with the modified tannin. The thermal properties of the modified lignin, tannin, and the bioresins were assessed by DSC and TGA. When the bioresins were cured at a high temperature (200 °C) by compression moulding, they exhibited higher thermal stability as well as an enhanced degree of cross-linking compared to the low temperature-cured bioresins. The thermal properties of the resins were strongly affected by the compositions of the resins as well as the curing temperatures.